College Algebra (6th Edition)

Published by Pearson
ISBN 10: 0-32178-228-3
ISBN 13: 978-0-32178-228-1

Chapter P - Summary, Review, and Test - Test: 2

Answer

Simplified form of given expression = 17 - 6x

Work Step by Step

7 + 2 [3(x + 1) - 2(3x - 1)] = 7 + 2[3x + 3 - 6x + 2] = 7 + 2[5 - 3x] = 7 + 10 - 6x = 17 - 6x Simplified form of given expression = 17 - 6x
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.